2015
DOI: 10.3747/co.22.2623
|View full text |Cite
|
Sign up to set email alerts
|

Pilot of Three Objective Markers of Physical Health and Chemotherapy Toxicity in Older Adults

Abstract: Background Patient function is a key part of the clinical decision to offer chemotherapy and has, in earlier studies,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Sample sizes ranged from 24 [39] to 12,979 [52]. Studies were globally represented; 24 studies from Asia [40-43, 46-48, 50, 53-56, 58-66, 68, 70], 14 from Europe [31-36, 38, 44, 45, 51, 57, 69, 71, 72], and 5 from North America [37,39,49,52,67].…”
Section: Resultsmentioning
confidence: 99%
“…Sample sizes ranged from 24 [39] to 12,979 [52]. Studies were globally represented; 24 studies from Asia [40-43, 46-48, 50, 53-56, 58-66, 68, 70], 14 from Europe [31-36, 38, 44, 45, 51, 57, 69, 71, 72], and 5 from North America [37,39,49,52,67].…”
Section: Resultsmentioning
confidence: 99%
“…Characteristics of included studies are presented in Table 1 . Eighteen studies were prospective cohort studies [24][25][26][27][28][29][30][31][32][33][34][35]38,41,43,[45][46][47][48][49]51,52], and nine were retrospective studies [36,37,39,40,42,44,50,51,53].…”
Section: Resultsmentioning
confidence: 99%
“…Mobility problems (i.e. walking impairment, and inability to walk more than one block) was associated with chemotherapy toxicity in two out of four studies [29,41]. Three out of nine studies [31,35,37] reported that having severe comorbid conditions was associated with chemotherapy toxicity.…”
Section: Chemotherapy Toxicitymentioning
confidence: 96%
See 2 more Smart Citations